2019
DOI: 10.1002/mus.26389
|View full text |Cite
|
Sign up to set email alerts
|

VCP myopathy: A family with unusual clinical manifestations

Abstract: Introduction: Valosin-containing protein (VCP) variants that affect muscle, bone, and the nervous system are termed multisystem proteinopathy. VCP myopathy is manifested as limb-girdle weakness, distal weakness and scapuloperoneal weakness. Methods: We reviewed clinical, genetic, and muscle biopsy data from 6 members of a family with VCP myopathy. Results: Clinical features of family members were complex and included dementia, myopathy, and hearing impairment. Ophthalmoplegia, ptosis, and dysphagia were presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Although previously VCP mutations were known to cause hereditary inclusion body myopathy (IBM), Paget's disease of the bone (PDB), and frontotemporal dementia (FTD), collectively known as IBMFTD [1], there are now reported cases of familial amyotrophic lateral sclerosis (ALS), hereditary spastic paraplegia (HSP), parkinsonism, and Charcot-Marie-Tooth Type 2 disease [3], thus confirming that VCP mutations are multisystem proteinopathies (MSP) [4]. Although there is such significant variability in VCP mutations and clinical presentations [5, 6], the disease is inherited in an autosomal dominant fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Although previously VCP mutations were known to cause hereditary inclusion body myopathy (IBM), Paget's disease of the bone (PDB), and frontotemporal dementia (FTD), collectively known as IBMFTD [1], there are now reported cases of familial amyotrophic lateral sclerosis (ALS), hereditary spastic paraplegia (HSP), parkinsonism, and Charcot-Marie-Tooth Type 2 disease [3], thus confirming that VCP mutations are multisystem proteinopathies (MSP) [4]. Although there is such significant variability in VCP mutations and clinical presentations [5, 6], the disease is inherited in an autosomal dominant fashion.…”
Section: Introductionmentioning
confidence: 99%
“…MSP5 with MATR3 mutation is characterized by marked impairment of finger extensor muscle groups, nasal voice, hoarseness, difficulty swallowing, muscle pain after exertion, and respiratory dysfunction 12 . MSP1 with VCP mutation may have facial muscle involvement, such as ptosis, and respiratory dysfunction 13 . Cases with VCP mutation may present with muscle weakness in various regions and should be treated with caution.…”
Section: Discussionmentioning
confidence: 99%
“… 12 MSP1 with VCP mutation may have facial muscle involvement, such as ptosis, and respiratory dysfunction. 13 Cases with VCP mutation may present with muscle weakness in various regions and should be treated with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a literature review on the clinical and genetic characteristics of previously reported ALS‐VCP cases (Table S1), 2,4–7,16,23–33 and illustrated mutation sites in VCP associated with ALS, IBMPFD, and other phenotypes (Figure S1). 2–5,7,16,20–86 A total of 59 cases have been reported, with the disease typically developing in patients in their 40s–50s, and 14 of the 33 cases survived without artificial respiration for more than five years. Given that the epidemiological studies of general ALS suggest that the peak prevalence is observed in patients in their 70s–80s, and that the median survival time is two to four years, 87–91 the ALS‐VCP cases might be characterized by relatively early disease onset and slow disease progression.…”
Section: Discussionmentioning
confidence: 99%